Effect of maltodextrin concentration and drying temperature on the characteristics of watermelon (Citrullus vulgaris S.) albedo instant drink enriched with telang flower (Clitorea ternatea) extract - Prabowo, Ulya Sarofa; Saraswati , Poppy (Anjoro: International Journal of Agriculture and Business, 2021)
Watermelon albedo is a food waste that still contains nutrients. The presence of nutritional compounds such as vitamins, minerals, citrulline and antioxidant components cause watermelon albedo potential processed into instant drinks. The addition of telang flower extract in watermelon albedo instant drinks aims to provide an attractive color of the drink, and telang flowers contain high antioxidant compounds. This study aims to determine the effects of maltodextrin concentration and drying temperature on the characteristics of instant drinks made from mixed watermelon albedo and telang flower extract and got the best treatment. This study used a Complete Randomized Design factorial pattern of 2 factors namely the concentration of maltodextrin (10%, 15%, 20%) and drying temperature (40 °C, 50 °C, 60 °C). The obtained data were tested using ANOVA and DMRT advanced tests. The results showed that the best treatment was on the concentration of maltodextrin 20% and drying temperature of 40 °C which produced instant drinks with a moisture content of 3.90%, ash content 0.83%, yield 17.69%, solubility 99.58%, vitamin C 2.89 mg.100g–1, antioxidant activity 30.76%, and organoleptic test of taste 4.15 (like-really like), color 3.65 (rather like-like) and aroma 3.55 (rather like-like).